Interurban on Robert Street (Minnesota Streetcar Museum; http://www.trolleyride.org, 1920)
578ab57216dc07bbe57528722cd9ea0a
St. Paul Southern interurban on streetcar tracks at the north end of the Robert Street bridge over the Mississippi River.
United States
Minnesota
Ramsey
Downtown
St. Paul
Mode of access: Internet.
Keywords: streetcars; Twin City Rapid Transit Co.; street scene; Transportation